Hemiarthroplasty in Intertrochanteric Femur Fractures: A Descriptive Study of Length of Stay and Postoperative Complications in a Peripheral Hospital Setting - Bobby Satria Aji; Muhammad Nazir Zubaidi; Alfian Marthunus (International Medical Journal Corp. Ltd, 2025)
Introduction: Intertrochanteric femur fractures in the elderly represent a significant clinical and socioeconomic challenge, particularly in resource-limited healthcare settings. The optimal surgical management remains debated, with hemiarthroplasty (HA) emerging as a viable alternative to internal fixation (IF) by allowing for immediate weight-bearing. This study aims to describe the postoperative outcomes, specifically length of stay (LOS) and complication rates, for patients undergoing HA for intertrochanteric fractures in a peripheral Type C hospital in Indonesia. Methods: A retrospective, descriptive case series was conducted on patients treated with primary HA for intertrochanteric femur fractures between mid-2024 and mid-2025. Data on patient demographics, postoperative LOS, and the incidence of postoperative complications were extracted from hospital medical records. Descriptive statistics, including mean, median, standard deviation (SD), range, frequencies, and percentages, were used for analysis. Results: A total of 26 patients were included in the study, with a mean age of 69.8 ± 8.1 years; 65.4% (n=17) were female. The principal finding was an exceptionally short mean postoperative LOS of 2.5 ± 1.0 days (median: 2.5 days; range: 1-4 days). However, the overall complication rate was high at 46.2% (n=12). The most common complications were postoperative anemia, recorded in 26.9% (n=7) of patients, and prosthetic dislocation, which occurred in 19.2% (n=5) of patients. Discussion: The observed ultra-short LOS is a significant deviation from international benchmarks and suggests a healthcare delivery model that prioritizes operational efficiency and rapid patient turnover, likely driven by resource constraints. This efficiency presents a compelling argument for the cost-effectiveness of HA in this specific context. The high complication rates, particularly for dislocation, are concerning but may reflect systemic factors such as surgical technique and the lack of supervised post-discharge care rather than an inherent failure of the procedure itself. Conclusion: Hemiarthroplasty for intertrochanteric fractures in a peripheral hospital setting facilitates a remarkably short hospital stay, offering substantial benefits for resource management. While associated with a high rate of manageable complications, the procedure represents a strategically advantageous treatment modality. Future efforts should focus on implementing targeted quality improvement initiatives to mitigate the risks of dislocation and anemia, thereby optimizing the overall value of this efficient surgical approach.